2015
DOI: 10.1080/10503307.2015.1053552
|View full text |Cite
|
Sign up to set email alerts
|

How and when feedback works in psychotherapy: Is it the signal?

Abstract: The use of OQ®-Analyst should be recommended in psychotherapeutic settings in Norway. Given the inconsistent results regarding the effect of warning signals, definitive conclusions about their effect may depend upon how and for whom it is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
(62 reference statements)
1
11
0
Order By: Relevance
“…We expected a stronger effect for FIT, mainly in the first episode. This would be in line with previous findings about trajectories of change, with most change occurring earlier rather than later in the treatment process indicating, the importance of the critical initial phase (see Miller et al [ 58 ] and also Amble et al [ 59 ] for an overview). Our finding suggests we should reconsider the Time factor.…”
Section: Discussionsupporting
confidence: 91%
“…We expected a stronger effect for FIT, mainly in the first episode. This would be in line with previous findings about trajectories of change, with most change occurring earlier rather than later in the treatment process indicating, the importance of the critical initial phase (see Miller et al [ 58 ] and also Amble et al [ 59 ] for an overview). Our finding suggests we should reconsider the Time factor.…”
Section: Discussionsupporting
confidence: 91%
“…Of the few studies that have attempted to isolate the effect of these multiple working parts, the findings are mixed. For example, whereas some studies suggest that the off-track alert signal may account for ROM's effect (Probst et al, 2013), others have failed to replicate this finding and have instead pointed to the feedback itself (e.g., the graph of patient progress) and the discussion of progress (or lack thereof) with the patient as the most facilitative aspects of ROM (Amble, Gude, Ulvenes, Stubdal, & Wampold, 2016). As should be clear, future research is needed to more precisely understand how ROM systems work, and to establish how best to achieve such positive effects in the most efficient manner.…”
Section: Using Rom To Improve Patient-level Care: Empirical Supportmentioning
confidence: 99%
“…Inconsistency can be caused by plausible heterogeneity on how therapists actually use ROM systems, by differences on the type of measures included in the system, or by the algorithms and formats of feedback it provides, the type of therapy, among many other factors. Research is needed that unveils how feedback is used and the mechanisms by which feedback influences outcomes (Amble et al., ; Janse et al., ; Moltu et al., ). Greenhalgh, Long, and Flynn () hypothesized that the lack of consistent impact of outcome feedback into practice may be due to the nomothetic nature of the assessment tools used, which provide too general information, whereas therapeutic processes are individualized.…”
mentioning
confidence: 99%
“…More recently, contradictory results were found. A number of studies (e.g., Amble, Gude, Ulvenes, Stubdal, & Wampold, ; Janse et al., ; Kendrick et al., ; Probst, Lambert, Dahlbender, Loew, & Tritt, ) showed that ongoing feedback about outcome progress and therapeutic alliance does not result in a better treatment outcome in CBT, except in the treatment of depression (Janse et al., ). On the other hand, outcomes were enhanced by providing treatment progress and alliance information to both clients and therapists in couple therapy (Anker et al., ; Reese, Toland, Slone, & Norsworthy, ) and in family therapy (Bickman et al., ; Cooper, Stewart, Sparks, & Bunting, ).…”
mentioning
confidence: 99%